Necrotising soft tissue infection of chest wall secondary to rib fractures - Patel, Bhavik (International Surgery Journal, 2023)
Necrotising soft tissue infection (NSTI) is a surgical emergency. We hereby present a rare case with NSTI of the chest wall secondary to rib fractures without any intra pulmonary pathology leading to a life-threatening surgical condition.